Structures, Lewis Acidities, Electrophilicities, and Protecting Group Abilities of Phenylfluorenylium and Tritylium Ions. Issue 3 (5th December 2016) - Follet, Elsa; Mayer, Peter; Berionni, Guillaume
Abstract: The isolation, characterization, and the first X‐ray structures of a fluorenylium ion and its Lewis adducts with nitrogen‐ and phosphorus‐centered Lewis bases are reported. Kinetics of the reactions of a series of fluorenylium ions with reference π‐, σ‐, and n‐nucleophiles of various sizes and nucleophilicities allowed the interplay between electronic and structural parameters on the electrophilicities of these planarized tertiary carbenium ions to be elucidated. Structure–reactivity correlations and extensive comparisons of their reactivities with those of di‐ and triarylcarbenium ions are described. Quantitative determination of the electrofugalities of fluorenylium ions revealed to which extent they are complementing tritylium ions as protecting groups and how their tuning is possible. Determination of the equilibrium constants of the Lewis adducts formation between pyridines of calibrated Lewis basicities and phenylfluorenylium and tritylium ions allowed the determination of their Lewis acidities and to showcase the potential of these carbon‐centered Lewis acids in catalysis. Abstract : The reactivities of phenyl‐fluorenylium ions toward nitrogen‐ and phosphorus‐centered Lewis bases and the structrures of their Lewis adducts are reported. Kinetic and thermodynamic investigations allowed to compare the Lewis acidities, electrophilicities and protecting group abilities of fluorenylium ions with those of tritylium and other carbenium ions.